Evaluation of ERP Systems Implementation Projects - Dyczkowski, Mirosław (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
The paper presents results of the author's research, intended to recognise the state of art practices in conducting Enterprise Resource Planning (ERP) systems implementation projects in Polish enterprises. The research was done from the perspective of companies in which the systems were implemented. Collected data, presented partially in this article, show a relatively positive picture of the projects, as in most cases time and cost limits were not overrun and functional objectives were met.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 8, s. 49-61